Always Better Control Method as Controlling for Medicine Inventory in Public Health Office - Marliza Noor Hayatie; Astia Putriana; Gati Anjaswari (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The purpose of this study is to control medicine supplies with the implementation of the Always Better Control (ABC) method in the Pharmaceutical Field of the Tanah Laut Regency Health Office. The availability of the medicine is part of the assessment the level of patient satisfaction with the health services of government agencies. Therefore, control of medicine supplies is important to do well so as not to cause financial losses to the country due to the accumulation of expired medicine in the inventory warehouse. This research is quantitative descriptive research. The data collected is primary data in the form of reports on medicine intake and medicine expenditure at the Tanah Laut Regency Health Office from January to December 2019. Numerically analyze data using the microsoft excel program. The results of this study showed that using the ABC method, the supply of medicine can be classified into three levels. Medicine that belongs to group A are types of medicine that are classified as having high use or sales (fast moving) as many as 6 types. Medicines that belong to group B are types of medicine with moderate sales of 6 types. Meanwhile, for medicine that belong to group C is a type of medicine whose sales are low (slow moving) as many as 8 types. The existence of medicine control with the ABC method provides convenience for management to consider the right investment value in ordering medicine needed by the people so as to improve the financial performance of the institution.